2021
DOI: 10.1111/apm.13102
|View full text |Cite
|
Sign up to set email alerts
|

Historical and contemporary views on cholera transmission: are we repeating past discussions? Can lessons learned from cholera be applied to COVID‐19?

Abstract: Cholera, a devastating diarrheal disease that caused several global pandemics in the last centuries, may share some similarities with the new COVID‐19. Cholera has affected many populations in history and still remains a significant burden in developing countries. The main transmission route was thought to be predominantly through contaminated drinking water. However, revisiting the historical data collected during the Copenhagen 1853 cholera outbreak allowed us to re‐evaluate the role of drinking‐water transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
1
5
0
1
Order By: Relevance
“…It is caused by Vibrio cholera serogroup O1 and O139. [1,2], however the current outbreak showed that O139 is more virulent than O1 serotype. The disease has very short incubation period i.e.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is caused by Vibrio cholera serogroup O1 and O139. [1,2], however the current outbreak showed that O139 is more virulent than O1 serotype. The disease has very short incubation period i.e.…”
Section: Introductionmentioning
confidence: 82%
“…[5] Moreover 1.3 to 4 million cases of cholera cases occur worldwide each year, out of which 21000 to 143,000 infected people die due to complication. [6] The reporting of cholera cases, always remained biased due to fear of international embargo, from most of countries of world.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cross-contamination or recontamination of water from unpolluted water sources at the point of use for hygiene purposes in the household might be an overlooked driver for cholera transmission behavior. 11,13,24,25,29 Open defecation behavior. Increased rates in open defecation practices among children during the monsoon season in all study areas are concerning, especially considering the risk of rainwater transporting feces to new sites.…”
Section: Discussionmentioning
confidence: 99%
“…Medical history teaching is essential in preparing young HCWs in managing future pandemics. 7,[73][74][75]…”
Section: Discussionmentioning
confidence: 99%